(untitled) (Statistics, Optimization & Information Computing, 2025)
The main contribution of this paper center a round searching for a lost target which moves among finite number of cells according to truncated Markov chain with continuous time , the searcher distributes the effort among the states and the purpose is to minimize the search effort and the probability of undetection at the same time.